Analysing the Role of Mentors in Entrepreneurship Education: Effective Support and Assistance - Efa Wahyu Prastyaningtyas; Sutrisno Sutrisno; Edy Djoko Soeprajitno; Abu Muna Almaududi Ausat; Suherlan Suherlan (Journal on Education, 2023)
Entrepreneurship education can help improve one's ability to innovate, build businesses and create jobs. However, not everyone has the ability to become a successful entrepreneur. Therefore, it is important for those who want to enter the business world to have a mentor who can help them achieve success. This research aims to provide new insights in the development of entrepreneurship education and the role of mentors in achieving business success. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study concluded that in entrepreneurship education, the role of mentors is crucial in helping aspiring entrepreneurs develop the skills and knowledge needed to start and manage a business. Mentors can provide direction, guidance and moral support to young entrepreneurs to help them overcome the challenges and difficulties faced in starting and running a business.